Oral Microbiology in Periodontitis 2018
DOI: 10.5772/intechopen.75747
|View full text |Cite
|
Sign up to set email alerts
|

Trojans in Oral Environments: Evidence of Molecular Mimicry in Oral Immunity

Abstract: Oral microbiome possesses more than 1000 microbial species that co-exist with human oral cavity. However, when there is an imbalance in microbial ecosystem, infection and inflammation occurs. Chronic inflammation produces constant antigen-cell presentation and reactivity T and B cell results in an adaptive immune response with high specificity cell-cell and antibody response producing an autoimmune disease by molecular mimicry. In this chapter, using just BLAST, shows self-epitopes (autoantigens) from differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Studies have shown that it has a 6 amino acid similarity to the Prevotella denticola protein containing the VWA domain. Another example would be the small 70 kDa nuclear ribonucleoprotein, which is also an autoantigen involved in SLE, which has a 7 amino acid similarity to Bacillus cereus [ 110 ]. Oral bacteria can also be involved in the development of diabetes by using molecular mimicry as one way to avoid the immune response.…”
Section: Mechanisms Of Autoimmunity Caused By Dysbiotic Changesmentioning
confidence: 99%
“…Studies have shown that it has a 6 amino acid similarity to the Prevotella denticola protein containing the VWA domain. Another example would be the small 70 kDa nuclear ribonucleoprotein, which is also an autoantigen involved in SLE, which has a 7 amino acid similarity to Bacillus cereus [ 110 ]. Oral bacteria can also be involved in the development of diabetes by using molecular mimicry as one way to avoid the immune response.…”
Section: Mechanisms Of Autoimmunity Caused By Dysbiotic Changesmentioning
confidence: 99%
“…For instance, the epitopes of P. denticola and Bacillus cereus have a high degree of similarity with the self-autoantigen Ro 60KDa, which is often detected in SLE and Sjögren’s syndrome (SS). In addition, P. gingivalis, Streptococcus spp ., and F. nucleatum have similar epitopes as the self-autoantigen pyruvate dehydrogenase complex E2 (PDC-E2), which is the possible mechanism underlying the initiation and progression of primary biliary cirrhosis (PBC) [ 113 ].…”
Section: Introductionmentioning
confidence: 99%